"You don't trust a government vaccine": Narratives of institutional trust and influenza vaccination among African American and white adults. (January 2019) - Jamison, Amelia M.; Quinn, Sandra Crouse; Freimuth, Vicki S.
Abstract: Vaccine confidence depends on trust in vaccines as products and trust in the system that produces them. In the US, this system consists of a complex network connecting pharmaceutical companies, government agencies, and the healthcare system. We explore narratives from White and African American adults describing their trust in these institutions, with a focus on influenza vaccine. Our data were collected between 2012 and 2014 as part of a mixed-methods investigation of racial disparities in influenza immunization. We interviewed 119 adults, primarily in Maryland and Washington, DC, in three stages utilizing semi-structured interviews (12), focus groups (9, n =  91), and in-depth interviews (16). Analysis was guided by grounded theory. Trust in institutions emerged as a significant theme, with marked differences by race. In 2018, we contextualized these findings within the growing scholarship on trust and vaccines. Most participants distrusted pharmaceutical companies, which were viewed to be motivated by profit. Trust in government varied. Whites described implicit trust of federal institutions but questioned their competency. African Americans were less trusting of the government and were more likely to doubt its motives. Trust in institutions may be fragile, and once damaged, may take considerable time and effort to repair. Highlights: Trust in flu vaccines may reflect trust in the institutions that produce them. Pharmaceutical companies are widely distrusted, often due to perceived motives. Trust in government differs by race, age and institution. White privilege may shape high levels of passive trust among Whites. Racialized history continues to shape current attitudes about institutions.